ANALISA KINERJA JALUR PEDESTRIAN DI JALAN RAYA UBUD - Kariyana, I Made; Pamungkas, Tri Hayatining; Putra, Gede Surya Dwija; Diana, Anita Intan Nura (JMTS: Jurnal Mitra Teknik Sipil, 2024)
Desa Ubud is a favorite tourist destination, therefore the pedestrian pathway needs to be carefully considered. Specifically, the pedestrian pathway along Jl. Raya Ubud which has a high volume of pedestrian activity, with the left side of the pathway being narrow due to obstacles such as electrical poles. On the other hand, the right side of the pathway is clear and spacious. This research aims to evaluate the level of service on both sides of Jl. Raya Ubud's pedestrian pathway. A quantitative descriptive method was used, following the guidelines of the Highway Capacity Manual (HCM) 2000, with observations and surveys conducted during busy morning (06.00-08.00), noon (11.00-13.00), and evening (16.00-18.00) hours. The analysis revealed that the left side of the pathway had a Level Of Service (LOS) of A in the morning, B in the afternoon, and C in the evening, while the right side maintained an LOS of A throughout. It is recommended that coordination between the Directorate General of Highways and the State Electricity Company be improved to address obstacles on the left side of the pedestrian pathway in Ubud Village. Abstrak Desa Ubud merupakan tujuan wisata favorit, oleh karena itu jalur pejalan kaki perlu diperhatikan dengan baik. Khususnya jalur pejalan kaki di sepanjang Jalan Raya Ubud yang memiliki volume aktivitas pejalan kaki yang tinggi, dengan sisi kiri jalur yang sempit karena adanya penghalang seperti tiang listrik. Di sisi lain, sisi kanan jalur tersebut bersih dan luas. Penelitian ini bertujuan untuk mengevaluasi tingkat pelayanan pada kedua sisi jalur pejalan kaki di Jalan Raya Ubud. Metode deskriptif kuantitatif digunakan, mengikuti pedoman Highway Capacity Manual (HCM) 2000, dengan pengamatan dan survei yang dilakukan pada jam-jam sibuk pagi hari (06.00-08.00), siang hari (11.00-13.00), dan sore hari (16.00-18.00). Hasil analisis menunjukkan bahwa sisi kiri jalan memiliki tingkat pelayanan (LOS) A pada pagi hari, B pada siang hari, dan C pada sore hari, sedangkan sisi kanan jalan memiliki LOS A sepanjang hari. Direkomendasikan agar koordinasi antara Direktorat Jenderal Bina Marga dan Perusahaan Listrik Negara ditingkatkan untuk mengatasi hambatan di sisi kiri jalur pejalan kaki di Desa Ubud.